Photoactive RuII-polypyridyl complexes that display sequence selectivity and high-affinity binding to duplex DNA through groove binding - Ghosh, Amrita; Das, Priyadip; Gill, Martin R.; Kar, Prasenjit; Walkar, Michael G.; Thomas, Jim A.; Das, Amitava (Chemistry A European Journal, 2011)
The duplex-DNA binding properties of a nonintercalating polypyridyl ruthenium(II) complex that incorporates a linear extended ligand with a catechol moiety has been probed with a variety of photo- and biophysical techniques. These studies reveal that the complex groove binds to DNA sequences biphasically, and displays binding constants equivalent to those of high-affinity metallointercalators. The complex also displays preferential binding to AT-rich sequences. Changes in the structure of the coordinated catechol ligand and the incorporation of intercalating ancillary ligands into the complex were found to modulate both the optical-binding response and binding parameters of the system, which indicates that the catechol moiety plays a crucial role in the observed enhancement to binding affinities.

Photophysical properties of ligand localized excited state in ruthenium(ii) polypyridyl complexes: a combined effect of electron donor-acceptor ligand - Verma, Sandeep; Kar, Prasenjit; Das, Amitava; Ghosh, Hirendra Nath (Dalton Trans, 2011)
We have synthesized ruthenium(II) polypyridyl complexes (1) Ru(II)(bpy)2(L1), (2) Ru(II)(bpy)2(L2) and (3) Ru(II)(bpy)(L1)(L2), where bpy = 2,2′-bipyridyl, L1 = 4-[2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl]benzene-1,2-diol) and L2 = 4-(N,N-dimethylamino-phenyl)-(2,2′-bipyridine) and investigated the intra-ligand charge transfer (ILCT) and ligand–ligand charge transfer (LLCT) states by optical absorption and emission studies. Our studies show that the presence of electron donating –NMe2 functionality in L2 and electron withdrawing catechol fragment in L1 ligands of complex 3 introduces low energy LLCT excited states to aboriginal MLCT states. The superimposed LLCT and MLCT state produces redshift and broadening in the optical absorption spectra of complex 3 in comparison to complexes 1 and 2. The emission quantum yield of complex 3 is observed to be extremely low in comparison to that of complex 1 and 2 at room temperature. This is attributed to quenching of the 3MLCT state by the low-emissive 3LLCT state. The emission due to ligand localized CT state (ILCT and LLCT) of complexes 2 and 3 is revealed at 77 K in the form of a new luminescence band which appeared in the 670–760 nm region. The LLCT excited state of complex 3 is populated either via direct photoexcitation in the LLCT absorption band (350–700 nm) or through internal conversion from the photoexcited 3MLCT (400–600 nm) states. The internal conversion rate is determined by quenching of the 3MLCT state in a time resolved emission study. The internal conversion to LLCT and ILCT excited states are observed to be as fast as ∼200 ps and ∼700 ps for complexes 3 and 2, respectively. The present study illustrates the photophysical property of the ligand localized excited state of newly synthesized heteroleptic ruthenium(II) polypyridyl complexes.

Photosensitization of nanoparticulate TiO2 using a Re(I)-polypyridyl complex: studies on interfacial electron transfer in the ultrafast time domain - Kar, Prasenjit; Banerjee, Tanmay; Verma, Sandeep; Sen, Anik; Das, Amitava; Ganguly, Bishwajit; Ghosh, Hirendra N. (Physical Chemistry Chemical Physics, 2012)
We have synthesized a new photoactive rhenium(I)-complex having a pendant catechol functionality [Re(CO)3Cl(L)] (1) (L is 4-[2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl]benzene-1,2-diol) for studying the dynamics of the interfacial electron transfer between nanoparticulate TiO2 and the photoexcited states of this Re(I)-complex using femtosecond transient absorption spectroscopy. Our steady state absorption studies revealed that complex 1 can bind strongly to TiO2 surfaces through the catechol functionality with the formation of a charge transfer (CT) complex, which has been confirmed by the appearance of a new red-shifted CT band. The longer wavelength absorption band for 1, bound to TiO2 through the proposed catecholate functionality, could also be explained based on the DFT calculations. Dynamics of the interfacial electron transfer between 1 and TiO2 nanoparticles was investigated by studying kinetics at various wavelengths in the visible and near infrared regions. Electron injection into the conduction band of the nanoparticulate TiO2 was confirmed by detection of the conduction band electron in TiO2 (Image ID:c2cp24105f-t1.gif) and the cation radical of the adsorbed dye (1˙+) in real time as monitored by transient absorption spectroscopy. A single exponential and pulse-width limited (<100 fs) electron injection was observed. Back electron transfer dynamics was determined by monitoring the decay kinetics of 1˙+ and Image ID:c2cp24105f-t2.gif.

Sequential energy and electron transfer in polynuclear complex sensitized TiO2 nanoparticles - Verma, Sandeep; Kar, Prasenjit; Banerjee, Tanmay; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry Letters, 2012)
Polynuclear–polypyridyl complexes exhibit a directional energy-transfer property that can improve their photosensitization activity. In the present work, the energy-transfer process is explored in a trinuclear Ru2∧Os1 complex using transient absorption spectroscopy. This study reveals an efficient excitation energy transfer from the terminal (RuII complex) to the core (OsII complex) region in the ultrafast time domain (400 fs–40 ps). The excitation energy funnel is useful in improving the functionalized core activity. This is evidenced in an interfacial electron-transfer study of Ru2∧Os1, Ru2∧Ru1, and Os1 complex sensitized TiO2 nanoparticle (TiO2 NP) systems. The intramolecular energy transfer causes sequential excitation of the core part of the Ru2∧Os1 complex, which leads to multiexponential electron injection into TiO2 NP. Besides this, the electronic coupling between the metal ion centers stabilizes the positive charge within the trinuclear complex, which results in a slow charge recombination reaction. This study shows that polynuclear complexes can be very useful for their panchromatic effects, unidirectional energy- and electron-transfer properties.